Mechanistic insights into robust cardiac IKs potassium channel activation by aromatic polyunsaturated fatty acid analogues - Briana M Bohannon; Jessica J Jowais; Leif Nyberg; Vanessa Olivier-Meo; Valentina Corradi; D Peter Tieleman; Sara I Liin; H Peter Larsson (eLife, 2023)
Voltage-gated potassium (KV) channels are important regulators of cellular excitability and control action potential repolarization in the heart and brain. KV channel mutations lead to disordered cellular excitability. Loss-of-function mutations, for example, result in membrane hyperexcitability, a characteristic of epilepsy and cardiac arrhythmias. Interventions intended to restore KV channel function have strong therapeutic potential in such disorders. Polyunsaturated fatty acids (PUFAs) and PUFA analogues comprise a class of KV channel activators with potential applications in the treatment of arrhythmogenic disorders such as long QT syndrome (LQTS). LQTS is caused by a loss-of-function of the cardiac IKs channel – a tetrameric potassium channel complex formed by KV7.1 and associated KCNE1 protein subunits. We have discovered a set of aromatic PUFA analogues that produce robust activation of the cardiac IKs channel, and a unique feature of these PUFA analogues is an aromatic, tyrosine head group. We determine the mechanisms through which tyrosine PUFA analogues exert strong activating effects on the IKs channel by generating modified aromatic head groups designed to probe cation–pi interactions, hydrogen bonding, and ionic interactions. We found that tyrosine PUFA analogues do not activate the IKs channel through cation–pi interactions, but instead do so through a combination of hydrogen bonding and ionic interactions.